Strategi Pembelajaran Guru pada Anak Berkebutuhan Khusus (Slow Learner) dalam Pendidikan Inklusi Di Sekolah Dasar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Children with special needs have their own perspective in learning a subject. Therefore, this article aims to find out learning strategies for children with special needs (Slow learners), where they need a separate strategy according to their needs. This study uses qualitative research with a phenomenological approach. The reason for using the phenomenological approach is because the researcher wants to explore information based on the experience of teachers in dealing with slow learner students. The data analysis technique was carried out in a qualitative descriptive manner. The data was analyzed in four components, namely data collection, data reduction, data presentation and conclusion drawn. This study found that they are: 1) Providing additional time Teachers who handle slow learner students provide additional time to complete assignments, 2) guiding slow learner students individually Individual guidance on certain materials has not been optimal due to the limitations of the media used, 3) Arranging the classroom environment Class V teachers also rearrange the classroom environment, especially for slow learner students. The arrangement of students' sitting positions is adjusted to conditions and situations that can support the Teaching and Learning Activities.